1988
DOI: 10.1063/1.340100
|View full text |Cite
|
Sign up to set email alerts
|

Defect mechanisms in degradation of 1.3-μm wavelength channeled-substrate buried heterostructure lasers

Abstract: Channeled-substrate buried heterostructure (CSBH) lasers which were purged from populations undergoing high reliability qualification have been studied in detail. Gradual and rapid degradation mechanisms leading to accelerated aging failure modes have been analyzed by transmission electron microscopy, convergent beam electron diffraction, electroluminescence, energy dispersive x-ray analysis, and chemical etching. The gradual degradation mode of CSBH lasers is characterized by (1) a gradual increase in room-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 52 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…Since the melted region usually extends vertically beyond the well, it not only destroys the quantum-well structure, in addition, the resolidified material also contains extensive lattice defects. 15 Occasionally, such degradation modes also occur inside the active stripe ͑away from the mirrors͒ at strong nonradiative recombination defects. [15][16][17] On the other hand, if the localized heating does not reach the melting temperature of InGaAs, it is most likely that In out diffusion from the InGaAs well into the adjacent GaAs barriers will occur as driven by the compositional discontinuity at the interfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the melted region usually extends vertically beyond the well, it not only destroys the quantum-well structure, in addition, the resolidified material also contains extensive lattice defects. 15 Occasionally, such degradation modes also occur inside the active stripe ͑away from the mirrors͒ at strong nonradiative recombination defects. [15][16][17] On the other hand, if the localized heating does not reach the melting temperature of InGaAs, it is most likely that In out diffusion from the InGaAs well into the adjacent GaAs barriers will occur as driven by the compositional discontinuity at the interfaces.…”
mentioning
confidence: 99%
“…Currently, one of the popular active structures for these devices uses a strained In x Ga 1Ϫx As/GaAs quantum well with xϳ0.2. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Although degradation of GaAs/AlGaAs, and InGaAsP/InP-based laser devices, has been studied extensively, [14][15][16][17] there are few studies of degradation of InGaAs/GaAs strained quantum-well lasers. [11][12][13] This study reports a generic degradation mechanism observed in 980 nm lasers, where In out diffusion ͑IOD͒ from the InGaAs quantum well into the GaAs barrier regions is observed.…”
mentioning
confidence: 99%
“…There are reports addressing the possibility of multiple thermal runaways during pulsed operation [15,[82][83][84][85]. Up to now, this possibility has been discussed ex post only on the basis of results obtained by transmission electron microscopy (TEM) of devices that were mechanically opened after COD.…”
Section: Cod Threshold In Pulsed Operationmentioning
confidence: 99%
“…(1,9). The velocity of the gliding motion has been shown to increase inversely with the bonding energy between atoms, and therefore, the bandgap energy.…”
Section: Literature Reviewmentioning
confidence: 99%